Effectiveness of government regulatory policies on technological upgrading a case study on a food processing plant - Ang, Agnes N.; Tabbada, Jose P. (Quezon City University of the Philippines Diliman, 2007)
Food safety is a public concern as it affects the nation's health and nutrition. It is gaining importance as a global issue due to significant changes in the food systems worldwide such as development of sophisticated technologies in the food industry, emergence of new harmful pathogens to humans, threats of bio-terrorism, changes in food handling and consumption, increase demand for food, expansion of international trade, and increasing public awareness towards demand for food safety. Policies are instituted by governments in different countries to address these issues concerning food safety (Unnevehr, 2003). Government food safety policies also influence the rate of adoption by the food industry (De Leon, et al., 2003). In some countries, government mandates on food safety triggers significant food safety innovations. In the US, a testing technology called Bacterial Pathogen Sampling and Testing Program is developed by Texas American Food Service Corporation for control of microbial pathogens in hamburger patty production lines. One of the drivers of the process innovation is to adhere with the USDA Food Safety Inspection Agency's zero tolerance policy on microbial adulterants. The government agency also provides collaboration with the innovator through parallel testing to validate and sell the efficacy of the technology (Salay, et al., 2003). In Canada, government forms partnerships with different stakeholders to come up with an innovative program such as the Canada Fight BAC campaign to effectively communicate food safety handling practices (FAO, 2002). In the UK, a testing technology that can be use to cut product recalls on food packaging materials that does not conform with EU standards is developed by Campden and Chorleywood Food Research Association under EC funding (Mercer, 2006). With food safety becoming a global concern, the study is undertaken to assess the effectiveness of the revised current Good Manufacturing Practice issued by BFAD using a local firm engaged in the processing of fish and fishery products as case study. The cGMP is one of the food safety policies being enforced by the country's government food regulatory agency. The firm is chosen so the author could help them in assessing its status on food safety compliance. The project objectives are the following : 1. To assess the effectiveness of the revised guidelines on the current Good Manufacturing Practices (cGMP) implemented by the Bureau of Food and Drugs Administration. 2. To study a local firm's adherence to the implementing guidelines on cGMP and whether these guidelines have bearing on the firm's technological upgrading or serve as driver for the firm to adopt innovations on food safety. The significance of the project are the following : 1. To serves as guideline for our local food regulating body for the review and formulation of better policies and programs that will strengthen the agency's food safety policies and its implementation aligned with improving the local industry's competitiveness in the domestic and international markets. 2. To help the firm under study to identify their weak points in complying with food safety regulations, particularly in cGMP. The expected outputs of the projects are : 1. A case study on the local firm engaged in processing of fish and fishery products. 2. Recommendations for the country's food regulatory agency regarding programs or action plans it can implement to strengthen its food safety policies as well as its implementation of GMP. 3. Recommendations for the firm on necessary improvements it need to implement in the food processing plant so as to better comply with regulations on cGMP. The methods used for the research include library and internet based research, interviews and plant inspection. Data are assessed qualitatively to come up with the research findings. International competitiveness and technological advancements of countries such as Japan, Korea, and the US are strongly associated with its government policies. According to Porter, the role of government in attaining international success in a particular industry is to influence or be influenced by each of the four determinants of competitive advantage either positively or negatively. These four determinants are factor conditions, demand conditions, related and supporting industries, and firm strategy, structure and rivalry. Factor creating mechanisms in Germany includes investing heavily on education such that they have wide available pool of highly educated and skilled human resources specializing in the needs of its local industries. In Sweden, government regulatory policies demanding high level of safety and environmental protection provide competitive advantage to Swedish firms such that they have been know for their safe products offerings. In the US, lax policies on media result on sophisticated marketing and advertising technology in America such that it has hold strong position in consumer packaged goods and services internationally. In Japan, government protectionist measures would also allow foreign rivals in the local industry forcing home grown industries to compete globally (Porter, 1990). In the examples cited, government policies are linked to technological upgrading of the particular nation. The food safety regulatory policy used for the study is A.O. 153 s. 2004 or the revised current Good Manufacturing Practice (cGMP) in Manufacturing, Packing, Repacking or Holding Food issued by BFAD. The cGMP is a food safety control that describes the methods, procedures, equipment, facilities, and controls for producing quality and safe foods under sanitary conditions. It is a "process-oriented regulation, which focuses on the technology and/or practices used in production to control the impacts and quality of the finished food product (Goldstein, 1994). The updated GMP is viewed as an important and urgent "tool" to push forward local industry's competitiveness and profitability. It serves as minimum mandatory and recommended requirements for food industry compliance and basis for inspection of food regulators. Main reference in the development of the country's cGMP is the US FDA regulatory policies in cGMP. The Bureau of Food and Drugs Administration (BFAD) is one of the main regulatory agencies tasked with implementing cGMP in foods and other food safety standards in the Philippines. The agency is created under virtue of R.A. 3720 or the Food, Drug and Cosmetic Act. The agency mandate is to ensure the safety and purity of foods, drugs and cosmetics being made available to the Filipino public. Other food regulatory agencies in the Philippines are BAFPS, BFAR, BAI and BPI. Other food safety control measures include 5S Good housekeeping practices, GAP, SSOP, and HACCP. The latter two items together with GMPs are mandatory requirements for export of fisheries and aquatic products for import in EU countries. The Philippines fisheries industry is ranked as 8th among the top-fish producing countries in the world for year 2003. This constitutes to 2.5 percent of the total world production of 146.27 million metric tons of fish and fishery products. For year 2004, contribution of the fishing industry to the National Economy is 2.3 percent of GDP at current prices and 4.2 percent at constant prices. The industry has also the second largest contribution to GVA in Agriculture, Fishery, and Forestry Group amounting to P111B or 14.9 percent and P48.7B or 21.6 percent for current and constant prices, respectively. The industry employes about 1,614,368 fishing operators based on the 2002 Census of Fisheries preliminary results.
For year 2004, the fishery industry total export value is 528M dollars and total import value is 94.5 M, registering a net surplus value of 433M dollars. Top fishery export products are tuna, prawn/shrimp, and seaweeds, which are high-value marine products in the world market. USA, Japan and Europe are the major export destinations of local marine products. Local demand for marine products such as octopus, crabs, lapu-lapu, cuttlefish/squid and lobster is also high. There are about hundreds processors of marine products most of which are small-scale enterprises engaged in the drying/smoking of fish. Fishery production and processing is listed as one the investment priority areas in the 2004 Investment Priority Plan (IPP) issued by DTI. The fish processing establishment used for the case study is operated by Sunseas Corporation. It is a private owned corporation engaged in the business of processing fresh frozen seafood products and repacking of dried/smoked fishes. The company started on October 1998 exporting frozen octopus then expands the business on 2003. Their product lines now include frozen cephalopods, frozen shrimps and prawns; frozen fishes and dried/smoked fishes. Main office and processing plant is located in Northbay Boulevard, Navotas. Their products, sold in wholesale, both serve the domestic and international markets. Seventy percent of sales are accounted from export sales. Although market potential for the business is said to be high, volume of market sales for year 2005 is around 200 metric tons, which is merely 20 percent of previous year's market sales. Slump in sales is attributed to different factors in the fisheries industry such as illegal method of fishing, increasing operational costs, very unstable prices of the commodity, competition from Asian fishery operators and processors, and stringent food safety standards in the international markets. The company is practicing Good Manufacturing Practices in its processing plant based on known industry practices and experience but is unregulated. They have not yet applied for registration with BFAD because there have been no requests from their clientele to present license issued by the agency. Their exclusive distributor handles processing requirements for export of their products. They also have not yet received notice from BFAD regulators that they need to be register with the regulatory agency and comply with its food safety policies such as A.O. 153 or the revised current Good Manufacturing Practice on Foods. They have not yet received copy of the latest regulatory order from the agency. Management of the company is aware that BFAD is the one implementing GMP policies on foods and expresses willingness to apply registration with the agency if they receive requests from their clientele and notice from the agency. Although this is the case, they are still implementing good manufacturing practices on the processing plant based on known industry practices that follow regulatory policies on GMP. As part of GMP implemented in the plant, they invested on sanitation technologies such as use of pressurized cleaning equipment, disinfectant chemicals, and worker's uniform. They also invested on packaging technologies such as vacuum packaging machine. Main drivers on implementing GMP and investing on said technologies are company's own initiative to give best quality products to consumers and buyer's requirements. Effects of GMP instituted in the plant include 0 percent product complaints as of this year and no added quality costs for them. Another significant effect of GMP instituted in the plant is that they are able to deliver high-quality, safe products that follow agreed upon specifications and that are free from any adulterations, such that, they are able to establish solid relationship with one of their top clients providing income for the company. In the case study presented, although BFAD already have issued guidelines for implementation of food safety policies such as cGMP, it seems that it is lacking on surveillance on unregulated food processing establishments. Recommendations of the author for the government agency are the following : 1. Collaboration with the local government units to serve as monitoring arm of BFAD to look onto food establishments in their municipalities if they are registered with the regulatory agency and if the food processor has complied with the agency's food safety requirements such as cGMP. 2. To make GMP compliance as a form of "branding" that can be used as marketing tool for companies that passed the food safety regulation and promote consumer awareness on food safety that could in turn push the food industry to comply with government policies and adopt food safety innovations. 3. To develop an incentive system for GMP compliance or non-compliance to encourage food operators in intensifying their GMP implementation. 4. To develop "industry-specific" GMPs for easy adaptation of the food safety regulatory policies especially for small-scale and medium-scale processors, and to create a "GMP advisory council" to provide support for these processors. 5. BFAD regulators should also be trained in technological advancements happening around the globe to facilitate better GMP inspection. On the other hand, the firm must also look into intensifying its food safety implementation as a responsibility to its consumers and as a market opportunity to broaden its market share. Recommendations of the author for the firm are the following : 1. The business should secure registration of LTO permit from BFAD and to register their product lines with the regulatory agency. This will enable them to gain entry to other markets, which in turn could provide increase in profits for the business as well. 2. The firm should intensify its GMP implementation to assure consumers or buyers that products they offer for sale are of the best quality and "safest" form. This would free them of any legal liabilities in case of product defects such as contamination. This would prepare them in securing approval of registration from other food regulatory agencies. This would also provide guarantee that they would remain competitive in the local and international markets where the trend is "food safety should be an innate quality of any product offerings".
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Food industry and trade; Food processing by-products industry; Technological innovations